Genome-wide identification of TPS and TPP genes in cultivated peanut (Arachis hypogaea) and functional characterization of AhTPS9 in response to cold stress - Zhong, Chao; He, Zehua; Liu, Yu; Li, Zhao; Wang, Xiaoguang; Jiang, Chunji; Kang, Shuli; Liu, Xibo; Zhao, Shuli; Wang, Jing; Zhang, He; Zhao, Xinhua; et al. (Frontiers in Plant Science, 2024)
Trehalose is vital for plant metabolism, growth, and stress resilience, relying on Trehalose-6-phosphate synthase (TPS) and Trehalose-6-phosphate phosphatase (TPP) genes. Research on these genes in cultivated peanuts (Arachis hypogaea) is limited. This study employed bioinformatics to identify and analyze AhTPS and AhTPP genes in cultivated peanuts, with subsequent experimental validation of AhTPS9's role in cold tolerance. In the cultivated peanut genome, a total of 16 AhTPS and 17 AhTPP genes were identified. AhTPS and AhTPP genes were observed in phylogenetic analysis, closely related to wild diploid peanuts, respectively. The evolutionary patterns of AhTPS and AhTPP genes were predominantly characterized by gene segmental duplication events and robust purifying selection. A variety of hormone-responsive and stress-related cis-elements were unveiled in our analysis of cis-regulatory elements. Distinct expression patterns of AhTPS and AhTPP genes across different peanut tissues, developmental stages, and treatments were revealed, suggesting potential roles in growth, development, and stress responses. Under low-temperature stress, qPCR results showcased upregulation in AhTPS genes (AhTPS2-5, AhTPS9-12, AhTPS14, AhTPS15) and AhTPP genes (AhTPP1, AhTPP6, AhTPP11, AhTPP13). Furthermore, AhTPS9, exhibiting the most significant expression difference under cold stress, was obviously induced by cold stress in cultivated peanut, and AhTPS9-overexpression improved the cold tolerance of Arabidopsis by protect the photosynthetic system of plants, and regulates sugar-related metabolites and genes. This comprehensive study lays the groundwork for understanding the roles of AhTPS and AhTPP gene families in trehalose regulation within cultivated peanuts and provides valuable insights into the mechanisms related to cold stress tolerance.